Evaluating gaps in consumer behavior research on organic foods: A critical literature review under Bangladesh context - Khandoker Mahmudur Rahman; Nor Azila Mohd Noor (Journal of Marketing and Consumer Behaviour in Emerging Markets (JMCBEM), 2016)
The global demand for organic foods has inspired the academicians and practicing professionals to explore consumer purchase behavior in this sector. The multiple promises that organic foods hold for the future - like sustainable food production, food safety, food security, nutrition and reduction of green-house gases - all might have influenced the recent rise of behavioral research in the organic food sector. Interestingly, Bangladesh has been a producer of organic foods since the early '80s; however, only a handful of studies could be traced that actually studied consumer behavior in this sector. The current paper explored the important roles that organic foods might play in Bangladesh, synthesized findings of past studies under Bangladesh context, and justified probable areas that might be investigated in future. Therefore, plausible gaps were explored in the existing literature pertaining to Bangladesh context and a tentative research agenda for future researchers was proposed.
Keywords: M30; M31; M39; 650; organic food purchase behavior; organic foods in Bangladesh; roles of organic foods in a developing country; behavior of organic foods consumer; green marketing and organic foods